2009
DOI: 10.1111/j.1582-4934.2008.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

A role for the transcription factor HEY1 in glioblastoma

Abstract: Glioblastoma multiforme (GBM), the highest-grade glioma, is the most frequent tumour of the brain with a very poor prognosis and limited therapeutic options. Although little is known about the molecular mechanisms that underlie glioblastoma formation, a number of signal transduction routes, such as the Notch and Ras signalling pathways, seem to play an important role in the formation of GBM. In the present study, we show by in situ hybridization on primary tumour material that the transcription factor HEY1, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 56 publications
(37 reference statements)
2
61
0
2
Order By: Relevance
“…BMP4 also induced the expression of Tnc, Sparc and Hey1 (Fig. 3D-F), genes known to be highly expressed in human gliomas (Hirata et al, 2009;Hulleman et al, 2009;Rempel et al, 1998). Interestingly, Tnc, which is known to strongly promote glioma invasion (Hirata et al, 2009), was upregulated over 100-fold after 18 to 72 h of BMP4 exposure in NSCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP4 also induced the expression of Tnc, Sparc and Hey1 (Fig. 3D-F), genes known to be highly expressed in human gliomas (Hirata et al, 2009;Hulleman et al, 2009;Rempel et al, 1998). Interestingly, Tnc, which is known to strongly promote glioma invasion (Hirata et al, 2009), was upregulated over 100-fold after 18 to 72 h of BMP4 exposure in NSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence supports the hypothesis that gliomas derive from a cancer stem cell (Das et al, 2008). Genes encoding the following proteins are expressed in gliomas: Tenascin C (Hirata et al, 2009;Mariani et al, 2001), Hey1 (Hulleman et al, 2009), SPARC (Rempel et al, 1998), Snail1 and Snail2 (Han et al, 2011;Yang et al, 2010), FGFR1 (Morrison et al, 1994), BMPR1a (Yamada et al, 1996), EGFR (Hegi et al, 2012), PDGFRa (Andrae et al, 2008;Nazarenko et al, 2012), Sox2 (Annovazzi et al, 2011), Podoplanin (Mishima et al, 2006), Gli3 (Shahi et al, 2008) and p75NGFR (Johnston et al, 2007). All these glioma-related genes were also expressed in normal NSCs during their transformation into invasive stem cells in the present study, including the constitutively expressed Fgfr1 and Bmpr1a genes (Panchision et al, 2001;Vescovi et al, 1993).…”
Section: Neural Stem Cell Invasion As a Model For Glioma Invasionmentioning
confidence: 99%
“…Notch signaling is a critical developmental pathway that controls neural stem cell fate and suppresses radial glia differentiation (Ehebauer et al, 2006). The notch signaling pathway is constitutively active in many high-grade gliomas and has been associated with progression of gliomas (Hulleman et al, 2009;Jeon et al, 2008;Shih and Holland, 2006;Zhang et al, 2008). Notch signaling from endothelial cells to hematopoetic stem cells (HSC) via expression of Notch ligands has been shown to drive the self-renewal characteristics and in vivo repopulation of long-term HSCs that lie adjacent to the vasculature (Butler et al, 2010).…”
Section: Brain Tumor-cell Endothelial-cell Signalingmentioning
confidence: 99%
“…Increased activation of the NOTCH signaling has been reported in several tumor types (18). Recent studies showed that this pathway induces the survival and/or proliferation in GBM and glioma cells (19)(20)(21)(22), and the expression of stem cell markers in glioma cells (21,22). According to these findings, the inhibition of this pathway leads to depletion of stem-like cells and to the block of the engraftment in embryonal brain tumors (23).…”
Section: Introductionmentioning
confidence: 96%